Audit delay drivers: Liquidity, leverage, size & auditor specialization - Raihan Firdaus; Bambang Subiyanto (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
Financial reports that exceed the deadline for the publication provisions of POJK number 14/POJK.04/2022 will experience delays in the publication of financial statements. Delay in the publication of financial statements indicates a problem with the company's financial statements, so it takes longer to complete the audit. The purpose of this study is to obtain empirical evidence and analyze the effect of liquidity, leverage, and company size on audit report lag with industry specialization auditors as moderating variables. Audit report lag is measured by the distance between the closing date of the company's financial statements and the date of the audit report. The population in this study was 559 companies with 15 companies as research samples, finally the total number of observations was 75. This study uses secondary data obtained from the Indonesia Stock Exchange and the official website of each company. Data collection in this study used purposive sampling technique. Data processing uses the WarpPLS 8.0 application. The results showed that liquidity and leverage have a significant positive effect on Audit Report Lag, company size has no significant effect on Audit Report Lag. Where as industry specialization, could be moderated liquidity and laverage on Audit Report Lag and fail to moderate company size on Audit Report lag.